(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the impact of the COVID-19 epidemic on the learning of 6th year students at Viet Nam University of Traditional Medicine, the academic year 2020-2021. Subjects and Methods: A cross-sectional descriptive study was conducted on 629 6th years students at Viet Nam University of Traditional Medicine in the academic year 2020-2021. The study period was from Mar 2021 to Nov 2021. Results: Most 6th year students (over 80%) were greatly affected in their studies by the COVID-19 epidemic. All waves of the epidemic had an impact on students’ theoretical and clinical learning. The level of satisfaction of 6th year students with online learning was 74.6%, with no statistically significant difference between male and female students (p>0.05). Over 80% of students said that online learning met the goals of the curriculum, while this rate of ensuring the output standards of the curriculum was over 70%. Conclusion: The COVID-19 epidemic has greatly affected students’ learning, leading to changes in students’ learning methods and plans.